Pedasaran Filsafat Hak Asasi Manusia Menurut Höffe and Lohmann - Otto Gusti Ndegong Madung; Adrianus Yohanes Mai; Winibaldus Stefanus Mere (Badan Strategi Kebijakan Hukum, 2025)
This article aims to philosophically justify the universality and the existence of human rights. Historically, the concept of human rights has evolved according to the context in which human rights are lived. One of the themes of debate is how human rights are justified or validated and how they can be universally accepted. Philosphers always have different opinions about what constitutes the basis of human rights. This article considers Höffe and Lohmann who sepciafically address this problem. Based on the philosophical approaches of Otfried Höffe and Georg Lohmann, this research emphasizes the universal validity of human rights. On the one hand, Otfried Höffe justifies the necessity of human rights in his anthropological approach of